"Imagine an Ignorance That Fights Back": Honoring Charles Mills, Our Inheritance and Charge. Issue 4 (October 2022) - Mueller, Jennifer C.
Critical race scholars lost a true comrade with the passing of renowned philosopher, Charles Wade Mills, on September 20, 2021. Along with his larger corpus, Mills' landmark text, The Racial Contract, remains a beacon to scholar-activists across many disciplines, sociology included. Here, I reflect personally and sociologically on our inheritance from Mills' incredible legacy. Beyond core concepts that will (and should) live on in sociologists' work, Mills' life and practice impart invaluable lessons. These include attuning to one's embodiment and pleasure, using mainstream tools for radical ends, and recognizing the need for transdisciplinarity in ongoing resistance to white supremacy.